2016
DOI: 10.1007/s13205-016-0442-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of endophytic bacteria isolated from in vitro cultures of peach and pear rootstocks

Abstract: Endophytes are microorganisms which live symbiotically with almost all varieties of plant and in turn helping the plant in a number of ways. Instead of satisfactory surface sterilization approaches, repeatedly occurring bacterial growth on in vitro rootstock cultures of peach and pear was identified and isolated as endophytic bacteria in our present study. Five different isolates from peach rootstocks were molecularly identified by 16S rRNA gene sequencing as Brevundimonas diminuta, Leifsonia shinshuensis, Sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 51 publications
(66 reference statements)
1
54
0
Order By: Relevance
“…Similarly, Rajendran et al (2008) isolated three endophytic bacteria from root nodules of Cajanus cajan and two out of three isolates were reported to produce siderophore. Liaqat et al (2016) also reported siderophore production by only 2 out of 7 endophytic bacteria isolated from peach rootstock. IAA values are mean of three replicates ± SD "-" means showed no production "+" means showed low production "++" means moderate production "+++" means high production…”
Section: Results and Discussion Isolation And Morphological Charactermentioning
confidence: 97%
“…Similarly, Rajendran et al (2008) isolated three endophytic bacteria from root nodules of Cajanus cajan and two out of three isolates were reported to produce siderophore. Liaqat et al (2016) also reported siderophore production by only 2 out of 7 endophytic bacteria isolated from peach rootstock. IAA values are mean of three replicates ± SD "-" means showed no production "+" means showed low production "++" means moderate production "+++" means high production…”
Section: Results and Discussion Isolation And Morphological Charactermentioning
confidence: 97%
“…Under Fe starvation, most microorganisms synthesize siderophores-low-molecular weight iron-chelating agents that solubilize Fe (III) and control intracellular Fe levels [69]. Liaqat and Eltem [70] identified the following species: Brevundimonas diminuta, Leifsonia shinshuensis, Sphingomonas parapaucimobilis, Brevundimonas vesicularis, and Agrobacterium tumefaciens as endophytes that are able to produce siderophores. Earlier, it was evidenced that Methylobacterium phyllosphaerae (isolated from the phyllosphere of lowland rice, India) produced a hydroxamate type of siderophores during Fe starvation, as well as tryptophan and tyrosine [69].…”
Section: Biosynthesis Of Factors Stimulating Plant Growthmentioning
confidence: 99%
“…To cope with the iron deficiency bacteria utilize siderophores which solubilize and bind Fe 3+ forming siderophore-Fe 3+ complexes that can be taken up by active transport mechanisms. Siderophores produced by endophytic and rhizospheric bacteria may limit bioavailability of iron to the phytopathogens thus constraining their growth [Liaqat and Eltem 2016]. In the genomes of all four plant-associated strains genes responsible for biosynthesis of enterobactin (entABEF), a catechol-type siderophore, were found ( Figure 2) [García et al 2015;Kanehisa et al 2017].…”
Section: Biocontrol Of Phytopathogensmentioning
confidence: 99%